Portraits and Caftans of the Ottoman Sultans - Atasoy, Nurhan; With the collaboration of Kinay, Irem (London Assouline Publishing, 2012)
From the founding of the Ottoman dynasty by Osman Gazi to Süleyman the Magnificent s legendary territorial conquests, the legacy of the 36 Ottoman sultans has undeniably left its mark throughout the course of history. Featuring exquisite portraits and lavishly decorated caftans, this large-format volume beautifully presents imagery that speaks to the magnificence of the Ottoman Empire and its powerful sultans.
Include Color Illustrations.
Keywords: Portraits -- Sultans -- Turkey -- Caftans